2018
DOI: 10.4236/wjv.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Feasibility of a New Low Cost Intra-Dermal Pre & Post Exposure Rabies Prophylaxis Protocol in Domestic Bovine in Jawali Veterinary Hospital, District Kangra, Himachal Pradesh, India

Abstract: Cattle are the backbone of household economy in rural areas of India and many of them die after bites by potentially rabid dogs, despite being given currently recommended five shots of intramuscular (IM) rabies vaccination as Post Exposure Prophylaxis (PEP). In 2016, seven of 21 bovine bitten by rabid dogs given IM rabies vaccination died due to rabies in Shimla Municipality. This scenario prompted the authors to look for a suitable protocol, based on human studies, to save animals. We tested various schedules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This is especially relevant in view of the fact that MSD Intervet (manufacturers of Nobivac ® Rabies vaccine) has been identified as one of the new suppliers for the WOAH rabies vaccine bank [ 27 ]. Hence, this study also aimed to check if there was better immune response as indicated by antibody titers for this vaccine as compared to other vaccines such as Raksharab and Rabivac Vet, used by other workers [ 14 , 15 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially relevant in view of the fact that MSD Intervet (manufacturers of Nobivac ® Rabies vaccine) has been identified as one of the new suppliers for the WOAH rabies vaccine bank [ 27 ]. Hence, this study also aimed to check if there was better immune response as indicated by antibody titers for this vaccine as compared to other vaccines such as Raksharab and Rabivac Vet, used by other workers [ 14 , 15 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals of Group II were immunized with 1 mL of rabies vaccine intramuscularly in the neck region on day 0 without a subsequent booster dose. Animals of Group III were immunized with 0.2 mL of rabies vaccine intradermally at the middle third of the neck region on day 0 and a booster vaccine on day 21 as per the studies of [ 13 , 14 , 15 ]. Animals of Group IV were immunized with 0.2 mL of rabies vaccine intradermally at the middle third of the neck region on day 0 without a subsequent booster dose.…”
Section: Methodsmentioning
confidence: 99%
“…In India, no rabies vaccine prophylaxis (Pre-Exposure) is done for domestic bovines. In our study on domestic cows and buffaloes, 5 that are left to graze in open pastures, out of 60 animals recruited, 25 animals (41.7%;17 cows and 8 buffalos), were having natural antibody titers without vaccination above 0.5 IU/ml in the range of 0.9 IU/ml and 15IU/ml by Rapid Fluorescent Focus Inhibition Test (RFFIT). While 12 unvaccinated cows tested at the HP University farm were having neutralizing rabies antibodies below 0.5 IU/ml (0.11-0.46 IU/Ml) because these cows were kept on an isolation farm since birth at Agriculture University, Palampur, Himachal Pradesh, India and did not have any contact with outside stray dogs.…”
mentioning
confidence: 97%
“…While 12 unvaccinated cows tested at the HP University farm were having neutralizing rabies antibodies below 0.5 IU/ml (0.11-0.46 IU/Ml) because these cows were kept on an isolation farm since birth at Agriculture University, Palampur, Himachal Pradesh, India and did not have any contact with outside stray dogs. 5 This clearly indicated that domestic cows and buffalos, when left for grazing in the open pastures, interact with the rabies virus carrier stray dogs 11 and get infected and have rabies antibodies in their blood without vaccination.…”
mentioning
confidence: 99%
See 1 more Smart Citation